(untitled) (European Journal of Pure and Applied Mathematics, 2011)
WeÂ obtain in this paper the solutions of the following difference equations Â x_n+1=((x_n-3)/(Â±1Â±x_n-1x_n-3)),n=0,1,..., where the initial conditions are arbitrary nonzero real numbers.